A Ruthenium Complex/Carbon Nanotube Based Electrode as the First Electrochemical Sensor for Simultaneous Sensing of D‐Penicillamine, 6‐Thioguanine and Catecholamines. Issue 6 (27th January 2016) - Mazloum‐Ardakani, Mohammad; Sheikh‐Mohseni, Mohammad Ali; Salavati‐Niasari, Masoud
Abstract: The electrochemical behavior of a synthesized Ru complex (RuL) was investigated at multiwalled carbon nanotubes modified carbon paste electrode. Some special properties of the electrochemical response of this modified electrode are suitable charge transfer rate, repeatability and independance of the pH of the solution. The modified electrode can catalyze the electrochemical oxidation of penicillamine (PA) by a heterogeneous chemical reaction between PA and RuL through catalytic EC' mechanism. The rate constant of this catalytic reaction was obtained as 1.4×10 6 M −1 s −1 by chronoamperometry. Because of increasing the anodic current and decreasing the oxidation potential of PA at the prepared modified electrode, this electrode was used as an electrochemical sensor for determination of PA. This sensor can determine the concentration of PA in the wide concentration range of 0.20–750.0 µM with the low detection limit of 80 nM. Simultaneous determination of PA and 6‐thioguanine in the presence of catecholamines is the other important advantage of this sensor. Abstract :